Porous structure of polyarylamide-based activated carbon fibres - Stoeckli, Fritz; Centeno, Teresa A.; Fuertes, A. B.; Muñiz, J. (My University, 1996)
Activated carbons were prepared from two polyarylamide fibres (Kevlar and Nomex) by carbonization and subsequent steam activation to 25 and 50% burn-off. The porous structure of the carbons has been investigated by physical adsorption of CH2Cl2 and N2O at 293 K and immersion calorimetry into liquids of different molecular dimensions.
The activated fibres have good sorptive capacities and relatively narrow micropores. The materials resulting from activation at low degrees of burn-off could therefore be of great interest in gas separation, owing to their molecular-sieve properties. Compared to industrial activated carbons, the fibres are hydrophilic and have small external surface areas.